(3QSGdI aj GddYhbGJs ((3oeUWai Hf eMeO GdHSfhj s)
(3ChdgG (B:s
(3eHJhQ GdChd hChd GdehLhO efgG (B: (3dYhb GdUfhHQ (B: (3jfaY ef TOI GdZK hGdSYGd hGdbF hGdChQGe hGdNhGfjb hGdHdZe GddRL hUfYJg (B: (3UeZ YQHi s
(3BNQgG (B:s
(3TQGH GdYfGH TYjQ ebThQ, bKGA hNjGQ hbQY ef cnd KdGKI jQnV hjWHN, hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B174 - (3U(B176s
(3GfXQgG eY GdJMaI GdLGeYI Qbe (B:"366"s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B111 s
Keywords: (3GdWHs